2014
DOI: 10.1074/jbc.m113.526152
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-interacting Protein 1 Increases Chemoresistance by Maintaining Inhibitor of Apoptosis Protein Levels and Reducing Reactive Oxygen Species through a microRNA-146a-mediated Catalase Pathway

Abstract: Background: Whether RIP1 directly contributes to chemotherapy response in cancer has not been determined. Results: RIP1 knockdown resulted in miR-146a-mediated catalase reduction, ROS induction, IAP degradation, and increased cisplatin cytotoxicity. Conclusion: RIP1 blunts the anticancer activity of cisplatin by releasing miR-146a-mediated catalase suppression. Significance: Our results establish a chemoresistant role for RIP1, and intervention within the RIP1-mediated pathway may be exploited for chemosensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…The V5-catalase expressing lentiviral vector was from Biodesign Institute and viruses were produced and packaged in HEK293T cells following the manufacturer's instruction (29). A lentiviral vector having no ectopic protein expression was used as a negative control.…”
Section: Lentiviral Vector Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The V5-catalase expressing lentiviral vector was from Biodesign Institute and viruses were produced and packaged in HEK293T cells following the manufacturer's instruction (29). A lentiviral vector having no ectopic protein expression was used as a negative control.…”
Section: Lentiviral Vector Infectionsmentioning
confidence: 99%
“…The sequence of miR-551b primer is: 5′-GCGACCCATACTTGGTTTCAG-3′. Gene expression was quantified using the 2 −ΔΔCt method (29).…”
Section: Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…Accumulating studies have supported RIP1 as a key moderator of cell survival signaling, while other reports have suggested a prodeath role of RIP1. 22,24,55 Wang et al 22 have found that RIP1 played a crucial role in survival through catalase-mediated ROS reduction and maintenance of inhibitor of apoptosis proteins, thus enhancing chemoresistance to cisplatin in human lung cancer A549 cells. The activation of necropotosis was verified by the induction of RIP1 and RIP3, which was abrogated by necropotosis inhibitor necrostatin-1.…”
Section: Discussionmentioning
confidence: 99%
“…23 RIP1 transfers signals provoked by various stresses or chemotherapeutic agents to go through survival and death pathways. 22,24 RIP1 was shown to induce TNF-α receptor 1 for subsequent NF-κB stimulation to initiate cell survival. 24 These antiapoptotic-, antiautophagy-, and necropotosis-related cell survival mechanisms usually correspond to nonpump MDR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation